Simulation of Radiation Dose Distribution in Radiodiagnostic Facilities Using FLUKA Monte Carlo Code - Zyan, Wildan Muhammad; Ridwan Ramdani; Moch. Nurul Subkhi (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2025)
This study investigates the application of Monte Carlo simulations using the FLUKA code to evaluate the radiation dose distribution in the radiodiagnostic facility of the Fatmawati Medical Check Up Clinic. The objective is to compare the simulation results with experimental measurements and assess the accuracy of the simulation method. The research was carried out in the Physics Modelling Laboratory, Integrated Laboratory of State Islamic University (UIN) Sunan Gunung Djati Bandung, using an HP Proliant ML350P server computer equipped with Intel® Xeon® CPU E5-2620 v2 @ 2.10GHz × 12 cores. The simulation involved modeling the radiation chamber and photon emission plane, configured to emit 9×10⁹ photons at an energy level of 60 keV. Scattered radiation doses were measured at several locations, corresponding to experimental measurement points for validation. The results showed a strong correlation and high level of accuracy between the simulation and experimental data, with a relative error of less than 1%.